Implementasi Nilai Nilai Al-Qur’an Dalam Pendidikan Karakter Usia Remaja - Nur Illahi (Jurnal Asy-Syukriyyah, 2019)
Al-Qur’an values in adolescent character education was one part that must be considered.Al-Qur’an was one of the means of character development.Therefore,the development of adolescent character education in accordance with the Qur’an is absolutely done.There were so many values in the Qur’an character values that can be taken to carry out Islamic education,because the values were certain to be relevant to the objective of Islamic education.The implementation of adolescent character education in the values of the Qur’an was a method of analytical research inlearning Islamic education.Data collection techniques in this research was literature study.In the Qur’an there were values contained in adolescent character education including adherence,responsibility,compassion,peace,fairness and social care the values of taqwa contained in religious character were complex character in education some method that can be used among others,targhib methods,stories,habituation,commands,prohibition,dialogue (debate) and qudwah.The purpose of this study was to determine the values of the Qur’an in the character education of adolescent in the learning of Islamic education.